Quality-Based SQL: Specifying Information Quality in Relational Database Queries. - Parssian, Amir; Yeoh, William; Ee, Mong Shan (Computer (00189162), 2015)
A Structured Query Language extension uses an estimator module to evaluate quality profiles that rate the accuracy and completeness of query results. Users receive information that matches their defined quality constraints and better serves their data needs.